3D imaging of cleared human skin biopsies using light‐sheet microscopy: A new way to visualize in‐depth skin structure. Issue 2 (27th January 2018) - Abadie, S.; Jardet, C.; Colombelli, J.; Chaput, B.; David, A.; Grolleau, J.‐L.; Bedos, P.; Lobjois, V.; Descargues, P.; Rouquette, J.
Abstract: Background: Human skin is composed of the superimposition of tissue layers of various thicknesses and components. Histological staining of skin sections is the benchmark approach to analyse the organization and integrity of human skin biopsies; however, this approach does not allow 3D tissue visualization. Alternatively, confocal or two‐photon microscopy is an effective approach to perform fluorescent‐based 3D imaging. However, owing to light scattering, these methods display limited light penetration in depth. The objectives of this study were therefore to combine optical clearing and light‐sheet fluorescence microscopy (LSFM) to perform in‐depth optical sectioning of 5 mm‐thick human skin biopsies and generate 3D images of entire human skin biopsies. Materials and Methods: A benzyl alcohol and benzyl benzoate solution was used to successfully optically clear entire formalin fixed human skin biopsies, making them transparent. In‐depth optical sectioning was performed with LSFM on the basis of tissue‐autofluorescence observations. 3D image analysis of optical sections generated with LSFM was performed by using the Amira ® software. Results: This new approach allowed us to observe in situ the different layers and compartments of human skin, such as the stratum corneum, the dermis and epidermal appendages. With this approach, we easily performed 3D reconstruction to visualise an entire human skin biopsy. Finally, we demonstrated that this method is useful to visualise and quantify histological anomalies, such as epidermal hyperplasia. Conclusion: The combination of optical clearing and LSFM has new applications in dermatology and dermatological research by allowing 3D visualization and analysis of whole human skin biopsies.